Do amniotic fluid leptin levels decrease in pregnancies with fetal trisomy 21? - Demir, A.; Saatli, B.; Cagliyan, E.; Solak, A.; Guclu, S. (Informa Healthcare, 2012)
The objective of this study was to find a possible correlation between Down syndrome and amniotic fluid leptin. We compared 2nd trimester amniotic fluid leptin levels of fetuses with normal karyotype and with trisomy 21. We retrospectively found 15 fetuses with Down syndrome and we randomly selected 48 fetuses with normal karyotype as controls from our perinatology record database, in order to analyse their 2nd trimester amniotic fluid leptin levels. Amniotic fluid leptin levels were analysed by enzyme-linked immunosorbent assay (ELISA). The results were evaluated by Mann-Whitney U test. It was found that amniotic fluid leptin levels did not show any significant difference between amniotic fluids of fetuses with normal karyotype and those with trisomy 21 (p = 0.061). Median level of leptin was 10.06 ng/ml (range 2.10-36.69) for trisomy 21 fetuses and 14.53 ng/ml (range 2.30-67.33) for normal fetuses. In conclusion, leptin levels were not found to change in the amniotic fluids of fetuses with trisomy 21. This excludes a possible involvement of leptin in pathogenic processes associated with trisomy 21 during the fetal period and its potential employment as a diagnostic tool.
Keywords: Amniotic fluid; Down syndrome; leptin; 2nd trimester